Pengaruh Komunikasi Interpersonal, Etika Kerja dan Keterlibatan Kerja Terhadap Kepuasan Kerja Karyawan Lembaga Perkreditasn Desa (LPD) - Oksiani, Ni Made; Purwaningrat, Putu Atim (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2023)
The purpose of this study is to find out the influence of interpersonal communication, work ethics, and work engagement on the job satisfaction of employees of the Village Credit Institute (LPD) of Sading Mengwi-Badung Customary Village. This research was conducted at the Village Credit Institute (LPD) of Sading Mengwi-Badung Customary Village. The size of the population and sample are respondents who have employees up to 45 people taken by the method of determining the sample that is saturated sampling. Data collection is done through observation, interviews and questionnaires. The problems that have been shared are further tested with research tools and continued with classical prediction tests, multiple linear regression analysis, determination, partial and simultaneous significance tests with t-tests and F-tests. Based on the results of the analysis found that interpersonal communication had a positive and partially significant effect on employee job satisfaction in LPD Desa Adat Sading. Work ethic has a positive and partially significant effect on employee job satisfaction in THE Sading Customary Village LPD. Work involvement has a positive and partially significant effect on employee job satisfaction in THE SADING Customary Village LPD. Interpersonal communication, work ethic and work engagement have a positive and significant simultaneous effect on employee job satisfaction in THE Sading Customary Village LPD.